DISSENSUS: UPAYA UNTUK MENGHADIRKAN PRAKTIK SASTRA DAN BUDAYA YANG LEBIH DEMOKRATIS - Ghanesya Hari Murti; Degita Danur Suharsono (Universitas 17 Agustus 1945 Surabaya, 2022)
Ranciere is a political thinker who wants to give a spirit of optimism in citizenship equality. This spirit sparks in his view of democracy which he emphasizes not in consensus but dissensus. This means that democracy focuces more on disagreement rather than agreement of the winner in electoral vote because for him democracy should instead focus on votes that were not won. This is an ethical question why those who are marginalized are not accomodated. Only by dissensus, appropriateness and distribution of socio-cultural roles always be transformative and dynamic. In literary works, marginalized voices are important because it is locus of conflict This means that there are undemocratic nuances in literary works which are also the main issue. On the other hand, this also proves that democracy is a struggle that is never final because there is no absolute victory, that is, it is impossible to win votes in total. Hence, there is always a reason why there are votes that are not won? As a result, the consensus of winners is constantly questioned through dissensus since there is disagreement, or reconsideration for the sake of conditions for equitable distribution of justice. Ranciere traces all the problems of democracy not only in the world of politics but also in culture and even literature, which is indeed is full of discrimination that perpetuates the social hierarchy. Thus, this paper wants to provide a conceptual framework for democratization practices in the literary and cultural space by referring to Ranciere's thoughts in order to prevent works not only good representations but also questioned majority-based truth.